2023
DOI: 10.1038/s41598-023-28990-6
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity classification using passively collected smartphone-based keystroke dynamics within multiple sclerosis

Abstract: Multiple Sclerosis (MS) is a progressive demyelinating disease of the central nervous system characterised by a wide range of motor and non-motor symptoms. The level of disability of people with MS (pwMS) is based on a wide range of clinical measures, though their frequency of evaluation and inaccuracies coming from objective and self-reported evaluations limits these assessments. Alternatively, remote health monitoring through devices can offer a cost-efficient solution to gather more reliable, objective meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Additionally, an analysis across several studies found that rates of missing GPS and accelerometer data did not differ by sex, education, or age; however, Black participants were missing more accelerometer data (Kiang et al, 2021). Notably, although missingness of keyboard input data (keystroke logging) has been documented across studies (Hoeijmakers et al, 2023; McNeilly et al, 2023), to our knowledge no study has examined mechanisms driving keyboard missingness. Overall, there are significant gaps in our understanding of whether psychological, sociodemographic, and study design factors are associated with missing data in passive smartphone sensing research, particularly among youth and clinical populations (Renn et al, 2018).…”
Section: Experience Sampling and Passive Smartphone Sensor Approaches...mentioning
confidence: 99%
“…Additionally, an analysis across several studies found that rates of missing GPS and accelerometer data did not differ by sex, education, or age; however, Black participants were missing more accelerometer data (Kiang et al, 2021). Notably, although missingness of keyboard input data (keystroke logging) has been documented across studies (Hoeijmakers et al, 2023; McNeilly et al, 2023), to our knowledge no study has examined mechanisms driving keyboard missingness. Overall, there are significant gaps in our understanding of whether psychological, sociodemographic, and study design factors are associated with missing data in passive smartphone sensing research, particularly among youth and clinical populations (Renn et al, 2018).…”
Section: Experience Sampling and Passive Smartphone Sensor Approaches...mentioning
confidence: 99%
“…Using one year’s worth of data, researchers found that participants with MS who had worse arm motor function had a higher latency between keypresses, and participants with MS who had a decreased processing speed corresponded with a higher latency using punctuation and backspace keys [ 50 ]. Using the same dataset, researchers were also able to estimate the levels of disease severity, manual dexterity, and cognitive capabilities from keystroke dynamics using a machine learning model that used three predictors (a time-related cluster, a cognitive-related cluster, and the number of times autofill was used) [ 51 ]. Participants with MS who were quicker to correct and adjust their texting had higher SDMT scores, an indicator of cognitive functioning, which helped with model predictions [ 51 ].…”
Section: Keystroke Dynamics and Affected Cognitive Domains In Neurode...mentioning
confidence: 99%
“…Using the same dataset, researchers were also able to estimate the levels of disease severity, manual dexterity, and cognitive capabilities from keystroke dynamics using a machine learning model that used three predictors (a time-related cluster, a cognitive-related cluster, and the number of times autofill was used) [ 51 ]. Participants with MS who were quicker to correct and adjust their texting had higher SDMT scores, an indicator of cognitive functioning, which helped with model predictions [ 51 ]. These studies show that keystroke dynamics can be used as potential biomarkers for MS before significant disease onset, which would allow for earlier treatments and preventative care.…”
Section: Keystroke Dynamics and Affected Cognitive Domains In Neurode...mentioning
confidence: 99%
“…Smartphones for people with MS have been used to investigate fatigue using tapping gestures [17], dexterity through pinching motions [18], and general progression of the condition through non-invasive keyboard gestures [19]. To the best of the authors' knowledge, force control for people with MS has not been investigated using smartphone screen measurements.…”
Section: Introductionmentioning
confidence: 99%